Obesity as a Risk Factor for the Severity of COVID-19 in Pediatric Patients: Possible Mechanisms-A Narrative Review - Dana Elena Mîndru; Elena Țarcă; Heidrun Adumitrăchioaiei; Dana Teodora Anton-Păduraru; Violeta Ștreangă; Otilia Elena Frăsinariu; Alexandra Sidoreac; Cristina Stoica; Valentin Bernic; Alina-Costina Luca (MDPI AG, 2024)
Obesity, the current pandemic, is associated with alarming rises among children and adolescents, and the forecasts for the near future are worrying. The present paper aims to draw attention to the short-term effects of the excess adipose tissue in the presence of a viral infection, which can be life-threatening for pediatric patients, given that the course of viral infections is often severe, if not critical. The COVID-19 pandemic has been the basis of these statements, which opened the door to the study of the repercussions of obesity in the presence of a viral infection. Since 2003, with the discovery of SARS-CoV-1, interest in the study of coronaviruses has steadily increased, with a peak during the pandemic. Thus, obesity has been identified as an independent risk factor for COVID-19 infection and is correlated with a heightened risk of severe outcomes in pediatric patients. We sought to determine the main mechanisms through which obesity is responsible for the unfavorable evolution in the presence of a viral infection, with emphasis on the disease caused by SARS-CoV-2, in the hope that future studies will further elucidate this aspect, enabling prompt and effective intervention in obese patients with viral infections, whose clinical progression is likely to be favorable.